Barriers and facilitators for general practitioners to engage in advance care planning: A systematic review. (December 2013) - De Vleminck, Aline; Houttekier, Dirk; Pardon, Koen; Deschepper, Reginald; Van Audenhove, Chantal; Vander Stichele, Robert; Deliens, Luc
Abstract Objective. The aim of this systematic review is to identify the perceived factors hindering or facilitating GPs in engaging in advance care planning (ACP) with their patients about care at the end of life. Design. Studies from 1990 to 2011 were found in four electronic databases (PubMed, CINAHL, EMBASE, PsycINFO); by contacting first authors of included studies and key experts; and searching through relevant journals and reference lists. Studies were screened, graded for quality, and analysed independently by two authors; those reporting the perception by GPs of barriers and facilitators to engagement in ACP were included. Results. Eight qualitative studies and seven cross-sectional studies were included for data extraction. All barriers and facilitators identified were categorized as GP characteristics, perceived patient factors, or health care system characteristics. Stronger evidence was found for the following barriers: lack of skills to deal with patients' vague requests, difficulties with defining the right moment, the attitude that it is the patient who should initiate ACP, and fear of depriving patients of hope. Stronger evidence was found for the following facilitators: accumulated skills, the ability to foresee health problems in the future, skills to respond to a patient's initiation of ACP, personal convictions about who to involve in ACP, and a longstanding patient–GP relationship and the home setting. Conclusion. Initiation of ACP in general practice may be improved by targeting the GPs' skills, attitudes, and beliefs but changes in health care organization and financing could also contribute.